Carbonate-oxygen pretreatment of waste wheat straw for enhancing enzymatic saccharification. (May 2021) - Chen, Hui; Mao, Jiangyun; Jiang, Bo; Wu, Wenjuan; Jin, Yongcan
Graphical abstract: Highlights: High-value utilization of straw-handling waste (WWS) in pulp mill was investigated. Na2 CO3 -O2 is a promising pretreatment to increase enzymatic hydrolysis of WWS. The pretreatment is simple and economical, and the chemicals are easy to recycle. The process promotes the sustainable pretreatment of WWS. Abstract: Waste wheat straw (WWS), as the main solid waste from straw-handling yard in pulp mill, is often managed by combustion or sanitary landfill, representing an inefficient use and causing a great threat to the environment. Therefore, it is highly desirable to develop a facile and cost-effective method for the efficient utilization of WWS. In this work, Na2 CO3 -O2 pretreatment was conducted to WWS for enhancing the sugar recovery by enzymatic hydrolysis. The results indicated that Na2 CO3 -O2 pretreatment showed high delignification selectivity at relatively low temperature (110 °C) and total titratable alkali (TTA) charge (12 %, as Na2 O), with the lignin removal and pretreatment yield of 42.0 % and 67.9 %, respectively. The low pH value of the spent liquor after Na2 CO3 -O2 pretreatment (∼ 8.8) prevented the severe alkaline degradation of carbohydrates. At a cellulase loading of 20 filter paper unit (FPU)/g-cellulose, the total sugar recovery based on oven dry matter of raw material was up to 66.1 %. Na2 CO3 -O2 pretreatment is considered to be an operable and cost-efficient biorefining process and represents a promising method for the value-added utilization of WWS.